(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The infl uence of new religious movements on modern religious situation in Kazakhstan on the whole as well as its infl uence on the ethno-confessional mentality, extremalization of conscience and behavior of Kazakhstan citizens is examined in the present article. Key words: new religious movements, extremism, ethnoconfessional identifi cation.